2002
DOI: 10.1086/339407
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity of Endemic Community Pediatric Group A Streptococcal Pharyngeal Isolates and Their Relationship to Invasive Isolates

Abstract: By use of molecular techniques, the genetic heterogeneity of 63 community pediatric pharyngeal group A streptococcal (GAS) isolates circulating within a 3-week period were compared with 17 contemporaneous invasive pediatric isolates. Pharyngitis isolates represented 16 pulsed-field gel electrophoresis (PFGE) patterns with 12 emm serotypes, and invasive isolates represented 10 PFGE patterns with 9 emm serotypes. One-fourth of the pharyngeal isolates (16/63) were identical to at least 1 invasive isolate; convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 29 publications
5
33
0
1
Order By: Relevance
“…Furthermore, tonsillitis in childhood has been proposed as the major reservoir for circulating strains with the potential of causing invasive infection (13). The mean age of the patients with tonsillitis in our study was considerably higher than that of patients in conventional pharyngitis surveillance studies established in pediatric clinics (13,39). However, this is probably of minor importance, since we did not find any significant correlation between age and the emm type distribution in the groups of patients with tonsillitis and invasive infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tonsillitis in childhood has been proposed as the major reservoir for circulating strains with the potential of causing invasive infection (13). The mean age of the patients with tonsillitis in our study was considerably higher than that of patients in conventional pharyngitis surveillance studies established in pediatric clinics (13,39). However, this is probably of minor importance, since we did not find any significant correlation between age and the emm type distribution in the groups of patients with tonsillitis and invasive infection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be recognized that although the differences may be explained by relative oversampling of some regions for invasive isolates or noninvasive isolates relative to the other, it seems unlikely that it could be the only explanation. In recently published studies, isolates from invasive and noninvasive infections were of similar emm types and prevalence (10,13,26,39). Others have investigated isolates from invasive and noninvasive infections without identifying any clones that were statistically associated with invasive infections (2, 6), although M1 (emm-1) streptococci have been described as disproportionately associated with severe infections (23).…”
Section: Discussionmentioning
confidence: 99%
“…Beres et al (6) recently reported a significant correlation between prophage content and chromosomal pulsed-field gel electrophoresis pattern in serotype M3 organisms. Closely related but distinct pulsed-field gel electrophoresis patterns have been identified in M28 strains by several investigators (12,15,21,50,55). Hence, we anticipated that M28 strains would be highly diverse in prophage-associated virulence gene content.…”
Section: Discussionmentioning
confidence: 92%
“…Several recent studies have examined GAS strains of various serotypes to determine whether there was a correlation between prophage-encoded virulence gene content and the ability to cause a specific disease (6,21,43,55). However, there has not yet been an analysis of prophage-encoded virulence gene content that employed large population-based samples focused solely on type emm28 GAS strains.…”
Section: Discussionmentioning
confidence: 99%
“…GAS thrives at human mucosal sites and also causes devastating invasive infections. Strains isolated from mucosal sites are genetically indistinguishable from invasive strains by standard assays, such as M protein serotyping and multi-locus sequence typing (89,90). However, these techniques index only a very small part of the genome, which means that they greatly underestimate the amount of genetic variation present.…”
Section: Expanded Understanding Of Virulence Factor Regulation Pathwaysmentioning
confidence: 99%